Extracellular Vesicle-Encapsulated MicroRNA-375 from Bone Marrow-Derived Mesenchymal Stem Cells Inhibits Hepatocellular Carcinoma Progression through Regulating HOXB3-Mediated Wnt/β-Catenin Pathway - Zhaoxia Yu; Ju Liu; Qiqi Fan; Jun Yu; Xiaoting Ren; Xiaobin Wang (Analytical Cellular Pathology)
Nowadays, microRNA-375 (miR-375) has been implicated in many types of cancers, including hepatocellular carcinoma (HCC), and the functions of miRNAs encapsulated by extracellular vesicles (EV) in HCC progression have also been extensively investigated. In this research, we aimed to probe into the mechanism of EV-encapsulated miR-375 from bone marrow-derived mesenchymal stem cells (BM-MSCs) in HCC progression. At first, miR-375 expression in HCC tissues and cells was detected using RT-qPCR, and miR-375 was overexpressed to specify the effects of miR-375 on the malignant phenotype of HCC cells. miR-375 was downregulated in HCC, and overexpression of miR-375 suppressed HCC cell growth. Then, BM-MSCs and EV were isolated and identified, and, EV were cocultured with HCC cells for further functional assays. It was found that miR-375 encapsulated by EV could restrict the malignant phenotypes of HCC cells. Furthermore, the downstream genes and signaling cascades involved in HCC growth were investigated. HOXB3 was determined to be a downstream target of miR-375, and upregulation of miR-375 decreased Wnt1 and β-catenin protein expression. Furthermore, HOXB3 blocked the repressive effects of miR-375 on HCC cells and Wnt1 and β-catenin expression. This study highlights that miR-375 encapsulated by EV inhibits HCC development via modulating the HOXB3/Wnt/β-catenin axis.